Sistem e-PnP Fakulti Teknologi Kejuruteraan (FTK), UTHM - Sulaiman, Amelia; Salamat, Mohamad Aizi (Applied Information Technology And Computer Science, 2021)
There are many files or records of teaching and learning at the Faculty of Engineering Technology (FTK) Universiti Tun Hussein Onn Malaysia (UTHM) produced each semester but the management among staff is still done manually which can cause problems in terms of safety, control, detection, management and document assessment. Therefore, the purpose of this project is to develop a web -based information management system that will be used by staff to handle the process of management and evaluation of teaching and learning documentation files more systematically. The project development methodology used is a prototype technique to ensure the data flow can support efficient document sharing, collaboration of work environment and activity management as well as the operation of teaching and learning files in FTK, UTHM more organized. The modeling system developed includes process models, data models and interface models suitable for information modules, tasks, documents and assessments for teaching and learning file management in line with the requirements of FTK, UTHM. Finally, the development of this e-PnP System helps to increase productivity and management of a more orderly and efficient academic environment.